Design and evaluation of an imager for assessing wound inflammatory responses and bioburden in a pig model - Dacy, Ashley (J Biomed Opt, 2019)
Our work details the development and characterization of a portable luminescence imaging device for detecting inflammatory responses and infection in skin wounds. The device includes a CCD camera and close-up lens integrated into a customizable 3D printed imaging chamber to create a portable light-tight imager for luminescence imaging. The chamber has an adjustable light portal that permits ample ambient light for white light imaging. This imager was used to quantify in real time the extent of two-dimensional reactive oxygen species (ROS) activity distribution using a porcine wound infection model. The imager was used to successfully visualize ROS-associated luminescent activities in vitro and in vivo. Using a pig full-thickness cutaneous wound model, we further demonstrate that this portable imager can detect the change of ROS activities and their relationship with vasculature in the wound environment. Finally, by analyzing ROS intensity and distribution, an imaging method was developed to distinguish infected from uninfected wounds. We discovered a distinct ROS pattern between bacteria-infected and control wounds corresponding to the microvasculature. The results presented demonstrate that this portable luminescence imager is capable of imaging ROS activities in cutaneous wounds in a large animal model, indicating suitability for future clinical applications.